Autonomous manoeuvring of personal mobility devices (PMD) - Lee, Jie Han (2019)
Autonomous manoeuvring of Personal Mobility Devices (PMD) is a desirable feature similar to that of autonomous vehicles where its benefits may include more free time and increase in safety for the rider and pedestrians. In this project, the aim is to build an autonomous manoeuvring system for the prototype of PMD using camera as the source information. This project will be built primarily on a Raspberry Pi computer, camera and ultrasonic sensor. By performing different functions on the camera’s input, a stimulated path would be detected and hence provides critical information as to control the prototype’s motor to move along the desired path. The various versions of the prototype’s manoeuvring system will be listed and evaluated to establish the best one that strikes a balance between the performance and cost. In addition, incorporating the path detection algorithm together with the obstacle detection using ultrasonic sensor allows for a more complete yet simple autonomous manoeuvring system.